Challenges and key research questions for yaws eradication. Issue 10 (October 2015) - Marks, Michael; Mitjà, Oriol; Vestergaard, Lasse S; Pillay, Allan; Knauf, Sascha; Chen, Cheng-Yen; Bassat, Quique; Martin, Diana L; Fegan, David; Taleo, Fasihah; Kool, Jacob; Lukehart, Sheila; et al.
Summary: Yaws is endemic in west Africa, southeast Asia, and the Pacific region. To eradicate yaws by 2020, WHO has launched a campaign of mass treatment with azithromycin. Progress has been made towards achievement of this ambitious goal, including the validation of point-of-care and molecular diagnostic tests and piloting of the strategy in several countries, including Ghana, Vanuatu, and Papua New Guinea. Gaps in knowledge need to be addressed to allow refinement of the eradication strategy. Studies exploring determinants of the spatial distribution of yaws are needed to help with the completion of baseline mapping. The finding that Haemophilus ducreyi causes lesions similar to yaws is particularly important and further work is needed to assess the effect of azithromycin on these lesions. The integration of diagnostic tests into different stages of the eradication campaign needs investigation. Finally, studies must be done to inform the optimum mass-treatment strategy for sustainable interruption of transmission.